Factors that contribute to job stress among workers in workplace: a study of Selia Selenggara Selatan Sdn Bhd (SSSSB) and United Precision Engineering, Components and Automation (UPECA) / Muhammad Fazli Idris and Nurul Huda Abdul Rasid - Idris, Muhammad Fazli; Abdul Rasid, Nurul Huda (Faculty of Business and Management, Universiti Teknologi MARA, 2014)
This study conducted to identify the factors that contribute to job stress among workers in workplace. The researchers have chosen Selia Selenggara Selatan Sdn Bhd (SSSSB) And United Precision Engineering, Components and Automation (UPECA) to represent this study. Researchers have listed four variables which are work life balance, work overload, job match and job insecurity as the independent variables and job stress as the dependent variable. The researchers distributed 108 set of questionnaires to respondents which are Selia Selenggara Selatan Sdn Bhd (SSSSB) And United Precision Engineering, Components and Automation (UPECA). This study discussed the factors that contribute to job stress among workers in Selia Selenggara Selatan Sdn Bhd (SSSSB) And United Precision Engineering, Components and Automation (UPECA) and those factors will be the outcome of this study. The finding and analysis were made based on Statistical Package for Social Science (SPSS) version 20.0 to analyze the data. The finding of this study proves that work life balance, work overload and job match can positively contribute to job stress. Work life balance appears to be the most influenced factor towards job stress in Selia Selenggara Selatan Sdn Bhd (SSSSB) And United Precision Engineering, Components and Automation (UPECA).